ChemInform Abstract: Catalytic Asymmetric α‐Iminol Rearrangement: New Chiral Platforms. Issue 12 (March 2015) - Zhang, Xin; Staples, Richard J.; Rheingold, Arnold L; Wulff, William D.
Abstract Among a series of 19 different asymmetric catalysts screened for the rearrangement of α‐hydroxy imines to α‐amino ketones, the zirconium complex of VANOL (ZRV) shows the best catalytic activity although aluminum and titan complexes of VANOL, VAPOL, and 7, 7′‐tBu2VANOL are also quite effective.